A hybrid cuckoo search algorithm in parallel batch processing machines with unequal job ready times - Majumder, Arindam (2020)
This paper deals with the problem of scheduling identical parallel batch processing machines. In this scheduling system, each machine processes a set of jobs in a batch simultaneously and each job in the batch is characterized by its processing time, ready time and job size. We propose a hybrid discrete cuckoo search (HDCS) algorithm to minimize makespan for this scheduling problem. The HDCS is constructed, based on a modified variable neighborhood search and cuckoo search algorithm. In the proposed algorithm, we present a modified Lévy flight in the cuckoo search to transform a continuous position in the HDCS into a discrete schedule for generating a new solution. The process parameters of the proposed HDCS are tuned by implementing the desirability-based Taguchi method to optimize both solution quality and run time. The results of exhaustive computational experimentation on a large number of randomly generated sparse as well as non-sparse problem instances show that the proposed algorithm is more effective and efficient than the state-of-the-art algorithms.